Redefining higher education: innovation, inclusion, and sustainable development during wartime - Tsybuliak, Natalia; Lopatina, Hanna; Popova, Anastasiia; Bohdanov, Ihor; Sychikova, Yana; Glazkova, Iryna; Khatuntseva, Svitlana; Nesterenko, Maryna; Hurenko, Olha; Mytsyk, Hanna; Petryk, Kristina; Kovachov, Serhii; et al. (TECHNOLOGY CENTER PC, 2024)
This monograph presents an in-depth study of how universities are leveraging their role as key players in achieving the Sustainable Development Goals. It begins with the context of Ukraine, namely the impact of the war on academic potential, an analysis of a wide range of socio-economic, socio-psychological, professional and personal challenges that arose during the war. To overcome these challenges, a roadmap for systemic reforms and the development of a sustainable institutional ecosystem is proposed based on the triple helix model, which combines people-centric and infrastructural strategies. The following narrative builds on this foundation, exploring the theme of inclusiveness and accessibility in education. In particular, it examines how Ukrainian higher education institutions implemented adaptive strategies during the ongoing war to create a barrier-free environment, thus ensuring full participation of all students and pedagogical staff. The monograph then moves on to a detailed discussion of the integration of STEM education, emphasizing its vital role in national revitalization and alignment with the global sustainable development goals. This chapter shows how STEM education can be a powerful catalyst for societal transformation, equipping students with the skills they need to meet current and future challenges. In addition, the text delves into the specialized field of nanotechnology education, advocating the synergy of education, science, and values. This innovative approach reconciles technological progress with ethical standards and sustainable practice, marking it as a new paradigm for training a highly skilled and responsible professional. Ultimately, the themes are synthesized through the harmonization of institutional culture, values, university development strategies and the Sustainable Development Goals. The case study of Berdyansk State Pedagogical University, which adopted the "University without walls" model during the war, shows how the introduction of core values into the university's mission can contribute to the development of a sustainable institutional ecosystem and more global motives in the development of communities and society. Overall, the monograph not only outlines the challenges Ukrainian higher education faced during the war, but also highlights innovative responses and the critical role these institutions play in promoting sustainable development. It aims to provide a roadmap for other educational institutions, demonstrating that even in times of crisis, higher education can and should be a beacon of hope and progress, a key driver in promoting sustainable development.
Keywords: Redefining higher education; innovation; inclusion; sustainable development during wartime